2010
DOI: 10.1353/eas.0.0016
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Effectiveness: Impact of Emotional Intellegence and Work-Family Role Conflict in Work Organizations in Nigeria

Abstract: This study investigated the impact of emotional intelligence and work-family role conflict on managerial effectiveness of managers in work organizations in Nigeria. The descriptive survey research method was adopted for the study. Instruments used for data collection in this study are: Emotional Intelligence Scale, Work-Family Role Conflict Scale and Managerial Effectiveness Scale. Linear Regression Analysis was used to test hypotheses that were generated for the study at 0.05 alpha levels. Finding reveals tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…By applying t-test according to gender it was found that there are no notable differences in experiencing WFC between males and females. These results did not give support for H 1 , but confirmed results obtained in previous studies (Akintayo, 2010;Frone, 2003;Karatepe et al, 2010). Given the fact that several studies identified the impact of gender on intention to leave an organization (Chen et al, 2018;Emiroğlu et al, 2015), in this study the authors tested if gender has an influence on turnover intentions.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…By applying t-test according to gender it was found that there are no notable differences in experiencing WFC between males and females. These results did not give support for H 1 , but confirmed results obtained in previous studies (Akintayo, 2010;Frone, 2003;Karatepe et al, 2010). Given the fact that several studies identified the impact of gender on intention to leave an organization (Chen et al, 2018;Emiroğlu et al, 2015), in this study the authors tested if gender has an influence on turnover intentions.…”
Section: Discussionsupporting
confidence: 61%
“…Research that has addressed gender differences and conflicts between work and family has yielded various conclusions. Some studies have shown that women express the presence of these conflicts more than men (Frankenhaeuser et al, 1989;Lundberg et al, 1994), while others pointed out that gender has no effect on the conflict between family and business life (Akintayo, 2010;Frone, 2003;Karatepe et al, 2010). Research in the field of hospitality industry indicated that female employees report higher levels of WFC and FWC than male (Fiksenbaum et al, 2010;Tromp & Blomme, 2014;Yavas et al, 2008).…”
Section: Impact Of Gender On Work-family Conflict and Turnover Intentionsmentioning
confidence: 99%
“…Though some previous studies (e.g. McElwain, Korabik, & Rosin, 2005;Ng, et al, 2009) found evidence proposing differences between genders in terms of WFC, some other studies concluded that males and females experience WFC at similar levels (Frone, 2003;Akintayo, 2010). According to Kabasakal and Bodur (2001), females are expected to experience more WFC compared to males in Nigeria where gender egalitarianism is low (Aycan & Eskin, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…The findings of studies about the effect of gender on WFC are complicated and it should never be considered simple (Voydanoff, 2002;Powell & Greenhaus, 2010). While some studies state that females experience WFC more often and at a higher level, some others indicate it has no impact at all (Frone, 2003;Akintayo, 2010). According to gender role theory, females are more likely to consider the family role as a component of social identity compared to males.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Though some previous studies (e.g. McElwain, Korabik, & Rosin, 2005;Ng, et al, 2009) found evidence proposing differences between genders in terms of WFC, some other studies concluded that males and females experience WFC at similar levels (Frone, 2003;Akintayo, 2010). According to Kabasakal and Bodur (2001), females are expected to experience more WFC compared to males in Turkey where gender egalitarianism is low (Aycan & Eskin, 2005).…”
Section: Discussionmentioning
confidence: 97%